Open penetrating external laryngotracheal injury and abdominal trauma by suicide attempt successfully treated with immediate intervention: A case report. (April 2021) - Kamidani, Ryo; Okada, Hideshi; Kato, Rina; Nishihori, Takesumi; Kuze, Bunya; Yoshida, Takahiro; Yoshida, Shozo; Ogura, Shinji
Abstract: An open penetrating external laryngotracheal injury (PE-LTI) is a rare life-threatening injury requiring immediate intervention. Penetrating injuries may cause tissue loss, which makes wound closure difficult sometimes. Here, we report the case of an open PE-LTI and abdominal trauma by suicide attempt. A 38-year-old Asian man with depression was found in his home after having cut his own neck and abdomen. He was transported to a regional trauma center and immediately intubated. On arrival, his blood pressure was 120/90 mmHg and heart rate was 120 beats/min. Physical examination revealed three cuts each on the neck and abdomen and no dysphonia. The patient's condition was diagnosed as an open PE-LTI, classified as group 5 on the Schaefer classification system and zone II on the Roon and Christensen classification system. He was also evaluated for possible mesenteric injury. We performed an emergency primary laryngotracheal repair and exploratory laparotomy. There was no obvious blood vessel injury, but soft and cartilage tissues were crushed and disconnected completely. On day 8, he underwent wound closure and tracheostomy on the caudal side of the wound. He was successfully weaned from mechanical ventilation on day 9, transferred to the general ward on day 13, decannulated on day 63, and discharged from the hospital thereafter for subacute care. In this case of severe neck injury with complete laryngotracheal separation, tissue losses were relatively minimal. Wound closure presumably occurred early in the absence of blood vessel injury. Highlights: We could close wounds of external laryngotracheal injury early because despite complete laryngotracheal separation, the sharp and horizontal lacerations by suicide attempt with a kitchen knife were not accompanied by significant tissue losses. Although jugular vein or vertebral artery injuries are common with neck trauma, the findings from our case indicate that early wound closure may occur in case of an open penetrating external LTI without blood vessel injuries. We think there is a need for a new classification system that considers the sharpness of the wound, the degree of tissue loss and disruption, and the nature of the object that causes the injury.